Customary Law and Indigenous Peoples' Rights: Challenges in the Age of Globalisation - Bakri, Muh (Journal of Indonesian Scholars for Social Research, 2024)
Customary law and the rights of indigenous peoples have an important role in maintaining cultural identity and local wisdom, especially in Indonesia, which has a diversity of customs. However, in the era of globalisation, customary law faces various challenges, from the legal, economic and social aspects. This article explores how customary law and the rights of indigenous peoples are trying to remain relevant amidst the influences of modernisation, globalisation, and harmonisation with national law. The research uses a qualitative approach by analysing several cases in different regions, which shows that the process of globalisation often results in the erosion of customary law, marginalisation of indigenous peoples, and exploitation of natural resources in indigenous territories. The findings also highlight the importance of recognising and protecting customary law in state regulations, as well as the need to strengthen the rights of indigenous peoples in order to adapt and remain resilient in the face of global challenges. Thus, strengthening customary law in the national legal system is essential to create a balance between modernity and tradition.